Integration of the Environmental Regulations and National Criminal Code and toward Accountability Criminal Law: Environmental Regulation - Ahmad Said (Prodi Ilmu Lingkungan Fakultas Sains dan Teknologi, 2025)
Study This aim For know How provision action criminal post Constitution environmental cluster job creation life as well as accountability absolute on action criminal Constitution Environment , as well as integration in the National Criminal Code. As for the research This use method juridical-normative , so that can concluded : 1). Action criminal (strafbaar feit) which includes each person is an individual or business entity, whether incorporated​ law or not​ bodied law according to Constitution Environment. Among others, Articles 98-120, acts without own legal permits / approval by the government, the occurrence of victims/ damage health, safety environment, officials who do not do supervision, and subjects law corporation, then on action criminal the including action criminal 2). Footing problem error in Constitution this is what is deviant from principle error with use accountability criminal absolute , has There is in a way juridical in National Criminal Code Article 37a, and formulated in the Job Creation Law cluster environment life as strict liability the one who is asleep in Article 88, and vicarious liability ( National Criminal Code Article 37b, and Article 116 of the Job Creation Law Upper LH cluster accountability substitute), besides criminal, there are also dropped criminal addition or action in the Environmental Law life .